KAJIAN RUANG KONFIGURASI DAN PERSAMAAN GERAK BENDA TEGAR TERSAMBUNG MELALUI TEORI GRUP - , Eko Firmansah; , Muhammad Farchani Rosyid, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In this thesis we have studied the configuration space and the equation of motion of rigid body and 3-dimentional articulated body by mathematical machinery. The configuration space of the considered system has been studied in the grouptheoritical framework. The equation of motion of mechanical system has been derived by using Euer-Lagrange equation, general Lagrange equation, as well as Euler- Poincar e reduction. Which method should be applied depends on the mechanical system under studied. So that, the equation of motion in this reasearch showed by variety ways. The configuration space and the equation of motion which has been oftained were those of two and n rigid bodies systems, and the two and n articulated bodies systems.